Improving grid behaviour. - Taylor, C.W.
In this paper, the author describes how the inglorious Summer-of-1996 blackouts taught the Western USA to improve emergency grid control and protection and to sharpen power network simulation techniques
Keywords: Western USA; Emergency grid control; Power grid behaviour improvement; Power grid protection; Power network simulation techniques